Two new species of Chroogomphus (Gomphidiaceae, Boletales) with biocultural importance in the Tlahuica-Pjiekakjoo culture from Central Mexico - Pérez-Moreno, Jesús; Martínez-Reyes, Magdalena; Martínez-González, César Ramiro; Ramírez-Carbajal, Elisette; Carrera-Martínez, Anaitzi; de La Fuente, Javier Isaac; Olvera-Noriega, Joan Windhoek; Ayala-Vásquez, Olivia (Phytotaxa, 2023)
The genus Chroogomphus has scarcely been studied in Mexico, with only one species reported in the country despite its great biocultural importance in native cultures. In this study, two new species of Chroogomphus are presented based on genetic and morphological characterization. The phylogenetic analysis with DNA sequences from nrITS region confirmed that C. conacytiensis sp. nov. and C. flavovinaceus sp. nov. are included in independent clades separated from other species within the subgenus Chroogomphus. Both species have great biocultural importance in the Tlahuica-Pjiekakjoo native culture from Central Mexico as edible taxa, and are associated with Pinus pseudostrobus in Quercus-Pinus and in Pinus hartwegii forests. Descriptions and photographs of the newly described species are presented.